2021
DOI: 10.1111/nph.17204
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive introgression: how polyploidy reshapes gene flow landscapes

Abstract: Summary Rare yet accumulating evidence in both plants and animals shows that whole genome duplication (WGD, leading to polyploidy) can break down reproductive barriers, facilitating gene flow between otherwise isolated species. Recent population genomic studies in wild, outcrossing Arabidopsis arenosa and Arabidopsis lyrata indicate that this WGD‐potentiated gene flow can be adaptive and highly specific in response to particular environmental and intracellular challenges. The mechanistic basis of WGD‐mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Similarly, increased dosage may ‘mask’ deleterious loads, especially in young polyploid species [117, 118]. Given the young age of WGD estimated for S. oconnori [110], these predictions implicate a genomic landscape vastly more porous than might be expected in their diploid counterparts [114]. This may also be an underappreciated mechanism promoting the hypothesized increased adaptability of polyploids to stressful or novel environments [119, 120].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, increased dosage may ‘mask’ deleterious loads, especially in young polyploid species [117, 118]. Given the young age of WGD estimated for S. oconnori [110], these predictions implicate a genomic landscape vastly more porous than might be expected in their diploid counterparts [114]. This may also be an underappreciated mechanism promoting the hypothesized increased adaptability of polyploids to stressful or novel environments [119, 120].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that polyploidy facilitates a greater degree of genomic exchange than may be typical of reproductively isolated diploid species [96]. For example, ploidy has been suggested to promote introgression in diploid-tetraploid crosses of Arabidopsis, due to a circumvention of dosage-mediated postzygotic isolation [97][98][99]. Increased introgression has also been supported among tetraploid-tetraploid crosses (as herein), with one potential mechanism being an increase in local recombination rates, and thus a relaxation of linkage as a component of purifying selection, as ploidy increases [100,101].…”
Section: (A) Parallel Divergence Versus Parallel Hybridization In Nepali Snowtroutmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genomic level, recent detailed understanding of gene flow following WGD supports the idea that WGD can cause the breakdown of species barriers present in diploids. Evidence for this has come from both plants ( Arabidopsis arenosa/Arabidopsis lyrata [ Schmickl and Koch 2011 ]) and animals (the frog genus Neobatrachus [ Novikova et al 2020 ], reviewed in Schmickl and Yant 2021 ). In both examples WGD led to niche expansion ( Molina-Henao and Hopkins 2019 ; Novikova et al 2020 ) and the invasion of particularly challenging environments relative to the diploid: in the case of polyploid frogs, the desert ( Novikova et al 2020 ) and polyploid A. arenosa , metal-contaminated mines and serpentine barrens ( Arnold et al 2016 ; Preite et al 2019 ; Konečná et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in Arabidopsis plants (35, 36) and Neobatrachus frogs (37) suggested that despite the apparent isolation of the diploid species, tetraploid lineages in those groups can hybridize. This suggests that polyploidy can mediate interspecific gene flow (38) . One explanation of this phenomenon in seed plants is based on the hypothesis that polyploidy permits breakdown of endosperm-based incompatibility, thus lifting the postzygotic barrier and allowing hybridization among species (39, 40) .…”
Section: Introductionmentioning
confidence: 99%